PENGARUH HARGA, KETEPATAN WAKTU PENGIRIMAN, DAN KUALITAS PELAYANAN TERHADAP LOYALITAS KONSUMEN PADA JASA PENGIRIMAN BARANG SHOPEE EXPRESS DI KOTA SERANG - Surti Zahra; Yoga Andred Dana Tirta; Tubagus Agus Khoironi (National Conference on Applied Business, Education, & Technology (NCABET), 2022)
The purpose of this study is that the price is expected to have a considerable influence on consumer loyalty, timeliness of delivery is expected to increase consumer loyalty, service quality is expected to increase consumer loyalty, and to determine consumer loyalty from price, timeliness of delivery, and quality of service. The research method used is a survey research method. The survey method is a quantitative method. The results of the t-test study, the price has a significant effect with the tcount > ttable (4.698 > 1.66071), delivery time has a significant effect with the tcount > ttable (2.885 > 1.66071), and service quality has a significant effect on the tcount < ttable (-0.199 < 1.66071). Price, timeliness of delivery and quality of service together affect consumer loyalty with a value of Fcount > Ftable (106.888 > 2.31).